A cross-sectional investigation of the age-related development of power exertion in the lower limb among Japanese speed skaters - Yuda, J.; Yokozawa, T.; Ono, E. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: The skating velocity has been confirmed to be affected by the external power output of a skater, as well as air and ice resistances (van Ingen Schenau, 1982; van Ingen Schenau et al., 1987; de Koning et al., 1992). In addition, skaters can attain the skating speed by propulsive support leg extension under the crouched skating posture with a small knee and trunk angle. Therefore, the ability of power exertion in the lower limb is an important factor for speed skaters. This study identified the characteristics of the age-related development of power exertion in the lower limb among speed skaters. Methods: In total, 118 skaters (67 men and 51 women) provided informed consent and served as the study subjects. The skaters participated in the 500-m race of domestic speed skating competition in Japan or a time trial. The skaters were divided into 6 groups based on their age for each sex. However, senior skaters (over 18 y old) were divided into 2 groups based on the average time of the 500-m race. The age and average time for each group (mean ± SD) were as follows: MG1, 9.8 ± 0.4 y, 58.48 ± 12.36 s; MG2, 11.6 ± 0.5 y, 49.34 ± 6.54 s; MG3, 14.1 ± 0.7 y, 43.26 ± 4.11 s; MG4, 16.8 ± 0.9 y, 39.04 ± 1.24 s; MG5, 20.1 ± 1.4 y, 38.03 ± 0.96 s; MG6, 23.4 ± 3.8 y, 36.18 ± 0.56 s; WG1, 9.4 ± 0.5 y, 66.68 ± 20.96 s; WG2, 11.8 ± 0.4 y, 49.87 ± 4.47 s; WG3, 13.9 ± 0.8 y, 45.89 ± 3.10 s; WG4, 16.8 ± 0.9 y, 42.90 ± 1.30 s; WG5, 21.3 ± 4.4 y, 41.60 ± 1.26 s; and WG6, 24.0 ± 3.9 y, 39.72 ± 0.50 s. The skaters performed double- and single-leg skate jump tests on a floor that required maximal effort. The vertical ground reaction forces were determined with a force platform (500 Hz). Results: In male skaters, the maximum vertical ground reaction force of double-leg gradually increased with growth; by contrast, that of a single-leg increased only slightly. On the other hand, in female skaters, the force of double-leg gradually increased with growth; however, no remarkable difference between groups was observed in that of a single-leg. Discussion: The level of power exertion in the lower limbs of both male and female speed skaters increased gradually as a result of physical growth and development. However, the development of the power exertion ability under the single-leg condition was lower than that in the double-leg condition.